Integrating Pedagogical Innovation and Strategic Management: Remediation Frameworks for Economics Education in South African Schools - Nana Yaw Brenya Agyeman; Venessa Aphane (Universitas Nurul Jadid, 2026)
This study explores effective remediation strategies that economics teachers can use to enhance students’ understanding and performance in South African schools. The research specifically examines how management practices, such as resource allocation, lesson planning, and teacher support, influence teaching effectiveness. A qualitative case study design was employed, involving 20 purposively selected experienced economics teachers from selected schools. Data were collected through semi-structured interviews and were analysed thematically to identify patterns in teaching and management strategies. Findings indicate that active learning, real-world applications, and context-sensitive teaching methods significantly improve students’ comprehension of economics. Additionally, effective school management—coordinating resources, monitoring student progress, and providing professional development—supports teachers in addressing learning challenges. These strategies help bridge gaps in understanding and foster higher student performance. The study highlights the importance of integrating innovative pedagogical approaches with strong management practices to enhance learning outcomes. Policymakers are encouraged to allocate resources strategically to address socioeconomic disparities and support schools in implementing both teaching and management improvements. By combining pedagogical innovation with effective educational management, this research provides actionable insights for enhancing economics education in South Africa.